Capecitabine-associated gastrointestinal ulceration, haemorrhage, and obstruction: a pharmacovigilance analysis based on the FAERS - Wang, Yuwei; Meng, Long; Liu, Xiao (Frontiers in Pharmacology, 2024)
Background Capecitabine has been reported to be associated with severe gastrointestinal (GI) adverse drug reactions (gastrointestinal ulceration, haemorrhage, and obstruction). However, statistical correlations have not been demonstrated, and specific GI adverse drug reactions, such as GI obstruction, are not listed on its label.We aimed to determine the associations between capecitabine and GI ulceration, haemorrhage, or obstruction among patients with breast cancer by examining data from the United States Food and Drug Administration Adverse Event Reporting System (FAERS).We performed disproportionality analysis of GI ulceration, haemorrhage, and obstruction by evaluating the reporting odds ratio (ROR) and the information component (IC) with their 95% confidence intervals (CIs).We identified 279 patients with capecitabine-associated GI ulceration, haemorrhage, or obstruction reported between January 1, 2004 and December 31, 2020. One-fourth of the cases of GI ulceration, haemorrhage, or obstruction resulted in death. Capecitabine as a drug class had disproportionately high reporting rates for GI ulceration [ROR 1.94 (1.71-2.21); IC 0.80 (0.60-0.99)], haemorrhage [ROR 2.27 (1.86-2.76); IC 0.99 (0.69-1.28)], and obstruction [ROR 2.19 (1.63-2.95); IC 0.96 (0.51-1.40)].Pharmacovigilance research on the FAERS has revealed a slight increase in reports of GI ulceration, haemorrhage, and obstruction in capecitabine users, which may cause serious or deadly consequences. In addition to the adverse reactions described in the package insert, close attention should be paid to GI obstruction to avoid discontinuation or life-threatening outcomes.Significant increases were observed in the reported rates of "gastrointestinal ulceration," "gastrointestinal haemorrhage," and "gastrointestinal obstruction" associated with capecitabine. GI obstruction was found to be a positive adverse reaction signal not recorded in the package insert.Although no clinical trials or observational studies have confirmed these signals, capecitabine's medication guidance should be reinforced to warn of GI toxicity, including GI ulceration, haemorrhage, and obstruction.More studies on capecitabine are needed to characterize its GI ulceration, haemorrhage, and obstruction risk factors and outcomes.